The Effect of Sustainability Report Disclosure on Company Value of Companies In The Indonesia Stock Exchange - Sulistyowati, Erna (Robust: Research of Business and Economics Studies, 2022)
Sustainability report disclosures consist of economic category, environmental category, and social category. This study aims to examine the influence of each category in disclosure of sustainability reports on firm value. This research uses quantitative methods. The type of data used is secondary data obtained from all companies listed on the Indonesia Stock Exchange for the 2017-2018 period. There are 30 sample companies that were produced from the purposive sampling method. The analysis technique used is Partial Least Square (PLS) with the help of SmartPLS 3.0 software. The results of this study conclude that only the economic category of sustainability report disclosures affected the influence on firm value in Indonesia. While the environmental category and social category in the disclosure of sustainability report have not influence on firm value,